2022
DOI: 10.1148/radiol.2021211546
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging and Hematologic Findings in Thrombosis and Thrombocytopenia after ChAdOx1 nCoV-19 (AstraZeneca) Vaccination

Abstract: An earlier incorrect version appeared online. This article was corrected on August 18, 2021. This case series reports six patients (4 men; median age 38 years; interquartile range 26-48) presenting with vaccine-induced thrombocytopenia and thrombosis beginning 3 to 26 days after receiving the first dose of the ChAdOx1 nCoV-19 (AstraZeneca) vaccine. The patients were admitted to a general hospital between 9 to 31 days after the first dose. All patients had strongly detected anti-platelet factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Specifically, eosinophilic lung disease, cerebral venous sinus thrombosis (CVST), pulmonary embolism, vaccine‐induced immune thrombocytopenia (VITT) and myocarditis were found to be associated with COVID‐19 vaccination. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, eosinophilic lung disease, cerebral venous sinus thrombosis (CVST), pulmonary embolism, vaccine‐induced immune thrombocytopenia (VITT) and myocarditis were found to be associated with COVID‐19 vaccination. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Among the cases with TTS in this systematic review, about 60% had no remarkable PMH of any personal or familial disease/risk factors, and about 24% had preexisting conditions. In addition, less than 30% of the cases had several regular medications with contraceptives as the most used medication [21][22][23][24][25][26][27][28] . However, the number of cases for each condition or medication is not enough to find a relationship between the pre-existing condition or regular medication and TTS risk post-ChAdOx1 nCoV-19 vaccination.…”
Section: Findings From the Systematic Review 321 Patient Characterist...mentioning
confidence: 99%
“…However, the number of cases for each condition or medication is not enough to find a relationship between the pre-existing condition or regular medication and TTS risk post-ChAdOx1 nCoV-19 vaccination. In addition to the common symptoms associated with administration of ChAdOx1 nCoV-19 vaccine with headache as the most common initial symptom (>44.2%) 2,11,[21][22][23][24][25][26] , cases in this systematic review reported having some uncommon initial symptoms, including hemorrhage/thrombotic problems (22.46%) 11,24,28,52,60,61 and discoordination/weakness/numbness/hemiparesis/cyanotic toes (19.6%) [21][22][23][29][30][31][37][38][39][40][41]48,52,54,56,62,63 as the most prevalent uncommon initial symptoms which could be a signal alert to be aware of VITTS. However, further study is needed to figure out a relationship between these initial symptoms and the risk of VITTS.…”
Section: Findings From the Systematic Review 321 Patient Characterist...mentioning
confidence: 99%
See 2 more Smart Citations